The Role of Basketry in Early Holocene Small Seed Exploitation: Implications of a Ca. 9, 000 Year-Old Basket from Cowboy Cave, Utah. Issue 1 (20th January 2008) - Geib, Phil R.; Jolie, Edward A.
Abstract : Despite ranking at the low end of the continuum in net caloric benefit relative to other foods, small seeds assumed great dietary importance in many parts of the world, including western North America. In a series of publications, Adovasio (1970a, 1974, 1980, 1986) argued that coiled basketry technology was invented in the eastern Great Basin during the early Holocene as a specialized food-processing technique. Coiled baskets are indeed useful for collecting and processing seeds, but it does not necessarily follow that they were originally designed for this purpose. A whole basket recently discovered at Cowboy Cave in southeastern Utah returned an AMS radiocarbon assay of 7960 ± 50 B.P., making it currently the earliest directly dated coiled basket from the Americas. This basket is not a parching tray and likely had nothing to do with harvesting seeds. We discuss the implications of this find with regard to tracking the temporal spread of coiled basketry technology in western North America and the role of coiled and twined forms in the initiation of small seed exploitation. Coiled and twined baskets for small seed processing may result from reconfiguration of existing technologies to create novel forms suited to a new food exploitation strategy.